Penambatan Nitrogen oleh Legume dan beberapa Implikasinya - Mappaona Mappaona (Buletin Ilmu Makanan Ternak, 1988)
Nitrogen Fixation by legume. In developing tropic countries, application of nitrogen fertilizer into pasture to improve the quality of herbage is not yet practiced widely due to the high of fertilizer cost and the low of animal farmers income. The use of legume in the form of mixed cropping in a pasture to improve the quality of pasture has been practiced in Australia and New Zealand since 50 years ago, and it still interested one to be studied and developed at present and the future. One of determinant factors as a key of the succesfull of mixed cropping in a pasture is the capability is not only depend on the kind of plant, but also influenced by many factors such as mineral nutrition, soil acidity, disease and insect, the potential of symbiosis and the adaptability of both the rhizobium and legume to soil and climate.